Echoes of Instability: How Geopolitical Risks Shape Government Debt Holdings - António Afonso; José Alves; Sofia Monteiro (CESifo GmbH, 2024)
Recognizing the profound influence of geopolitical risks and world uncertainty on financial investment behaviour, this study uses a comprehensive approach to assess the impact of rising geopolitical risk on sovereign debt holdings for a panel of 24 OECD economies from Q1 2004 to Q4 2023. To do so, we employ Ordinary Least Squares (OLS) fixed effects and Quantile Regression techniques within a panel data framework to capture the nuanced effects on both domestic and foreign entities. We find that escalating geopolitical tension decreases government debt holdings among domestic entities, notably domestic Banks, while foreign investors increase their ownership. This phenomenon is more pronounced for high proportion levels of debt in investor's portfolios. Our results allow us to conclude that while domestic economic agents display clearer risk aversion, foreign economic agents have a more risk-taking behaviour in what concerns the financial investment on government debt.
Keywords: C23; E44; G32; H63; 330; sovereign debt; geopolitical risk; world uncertainty; OLS; quantile regression